Synthesis of micro-sized shell-isolated 3D plasmonic superstructures for in situ single-particle SERS monitoring. Issue 15 (5th April 2016) - Zhang, Kun; Zhao, Jingjing; Ji, Ji; Liu, Baohong
Abstract : We report a sensitive single-particle SERS system enabling real-time and in situ observation of Au-catalyzed reaction processes without the interference from photocatalysis. Abstract : A single-particle SERS system enabling real-time and in situ observation of Au-catalyzed reactions has been developed. Both the catalytic activity and the SERS effect are coupled into a single bi-functional 3D superstructure comprising Au nanosatellites self-assembled onto a shell-insulated Ag microflower core, which eliminates the interference from photocatalysis.